2008
DOI: 10.1007/s00542-008-0749-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation on contact between the droplet and the slider at head-disk interface based on water-hammer pressure model

Abstract: To understand the cause of read/write error due to lube accumulation, a model to simulate the slider's response to the contact impact, which can occur between a lubricant droplet on the disk and a slider, was developed. The contact impact model is based on the water-hammer pressure model with an additional damping force, where the wave-shock pressure is assumed to function as the contact pressure, and the damping force defines the damping characteristics of the impact which are due to the lubricant's high visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…3. The light contact or lubricant surfing has been widely discussed (Vakis et al 2009;Ng et al 2009;Canchi and Bogy 2010;Li et al 2010). In order to extract information from the weak signal in the region III in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The light contact or lubricant surfing has been widely discussed (Vakis et al 2009;Ng et al 2009;Canchi and Bogy 2010;Li et al 2010). In order to extract information from the weak signal in the region III in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Juang and Bogy (2007) investigated the relationship between air bearing surface design and thermal actuation of a slider. More recently work can be found in (Xu et al 2009;Hua et al 2009;Vakis et al 2009;Shiramatsu et al 2009;Li et al 2009;Tani et al 2009;Ng et al 2009;Canchi and Bogy 2010;Knigge et al (2006); Li et al 2010;Canchi and Bogy 2010). Although the above studies have clarified many aspects of current-induced thermal pole tip protrusion, there are still many areas lacking of understanding.…”
Section: Introductionmentioning
confidence: 95%
“…The accumulated lubricant on the slider surface may transfer onto the disk surface to form a droplet there. And, the slider and the lubricant droplet might make contact, which might induce a small vibration of the slider, causing a signal jump in a hard disk drive [7,8]. Figure 3 shows the air flow pattern at 0.9 h, reverse flow and stagnation line on the whole ABS at the disk inner diameter (ID), middle diameter (MD) and outer diameter (OD).…”
Section: Air Flow Pattern On Abs Reverse Flow and Stagnation Linesmentioning
confidence: 98%
“…This is because the lubricant layer not only consumes valuable head/disk spacing and modifies the effective ABS profiles, but also because it may impose other negative effects such as flying stiction on the slider's flying dynamic performance. Recent research has indicated that the contact between the lubricant on the disk and the slider could cause the slider to vibrate, which would result in the read/disk signal loss that is usually observed in hard disk drive failure [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…At this small clearance flying instability, which results in a few nanometers of clearance variation, may cause read/write errors due to the high sensitivity of magnetic recording performance to clearance. In addition to direct contact between head and disk, collision between a lubricant droplet and head may cause vibrations and induce a read/write "signal jump" such as reported by Li et al [1]. Fowler and Geiss [2] observed droplets of OC (alkane) on the head that can cause the stiction at the HDI with a visualization setup.…”
Section: Introductionmentioning
confidence: 98%